Successful scaling of climate solutions requires qualified human skills and creative partnerships. - Tepa-Yotto, Ghislain; Dalaa, Mustapha; Obeng, Faustina (2024)
This report synthesises climate solutions promoted by the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project in Ghana. The solutions are prioritised and co-designed following a rigorous decision making process. The report highlights the building blocks of an inclusive and sustainable scaling model. It underlines how boosted human capabilities, effective partnerships and improved synergies can generate tangible outcomes for scaling climate information services and climate smart agriculture technologies towards improved food systems resilience.